Active feldspar powder, preparation method and application of active feldspar powder in cement stabilized macadam mixture
High gel-active active feldspar powder is prepared through high-temperature calcination and mechanical grinding, and applied it to cement-stabilized gravel mixture, which solves the problem of solid waste treatment of feldspar powder and achieves high-value resource utilization and sustainable improvement.
Patent Information
- Application Number
- CN202411921356.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-03-28
AI Technical Summary
As a by-product of the lithium battery industry, feldspar powder occupies land resources and is costly, so it is necessary to find efficient consumption treatment methods.
Through high-temperature calcination and mechanical grinding composite processes, active feldspar powder with high gel activity was prepared and applied as auxiliary gelling material to cement-stabilized gravel mixtures.
The high-value utilization of industrial solid waste resources has been achieved, the amount of cement is reduced, and the production cost is reduced, and the exploitation and utilization of non-renewable resources has been reduced, the ecological environment is protected and the sustainability of cement has been increased.
Smart Images

Figure BDA0005208116410000051 
Figure BDA0005208116410000061 
Figure BDA0005208116410000071
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of road engineering, and in particular to an active feldspar powder, a preparation method and application thereof in a cement-stabilized crushed stone mixture. Background Art
[0002] With the rapid development of the lithium battery industry, its byproduct feldspar powder has become a new type of bulk solid waste. If the feldspar powder is stored, it will not only occupy a large amount of land resources, but also increase the disposal cost. Therefore, it is urgent to carry out the disposal of feldspar powder. Summary of the invention
[0003] The purpose of the present invention is to provide an active feldspar powder, a preparation method and application thereof in a cement-stabilized crushed stone mixture. The active feldspar powder prepared by the method of the present invention has high gelling activity. The active feldspar powder is applied as an auxiliary cementitious material in a cement-stabilized crushed stone mixture, which can realize high-value utilization of industrial solid waste resources and reduce cement consumption, thereby reducing production costs.
[0004] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0005] The present invention provides a method for preparing active feldspar powder, comprising the following steps:
[0006] calcining the feldspar powder raw material at 1050-1300° C. to obtain calcined feldspar powder;
[0007] The calcined feldspar powder is coarsely ground to obtain coarsely ground feldspar powder with a particle size of ≤1.18 mm;
[0008] The coarsely ground feldspar powder is finely ground to obtain the active feldspar powder; the conditions for the fine grinding include: the mass ratio of the coarsely ground feldspar powder to the grinding body used for fine grinding is 1 to 3:1, the rotation speed is 600 to 900 rpm, and the time is 45 to 75 minutes.
[0009] Preferably, the feldspar powder raw material includes the following phases: 40-55wt% quartz, 40-55wt% albite and 4-10wt% potassium feldspar.
[0010] Preferably, the indicators of the feldspar powder raw material include: particle size ≤ 1.18 mm, specific surface area of 50 to 200 m 2 / kg, the 28d compressive strength activity index is 50-65%, and the 28d flexural strength activity index is 60-80%.
[0011] Preferably, the feldspar powder raw material is dried before calcination; the drying temperature is 100-120°C.
[0012] Preferably, the calcination time is 0.5 to 1.5 h; the calcination is carried out in an air atmosphere.
[0013] The present invention provides an activated feldspar powder prepared by the preparation method described in the above technical solution.
[0014] Preferably, the indexes of the activated feldspar powder include: the specific surface area is 568 - 711 m 2 / kg, the 28-day compressive strength activity index is 75 - 85%, and the 28-day flexural strength activity index is 87 - 98%.
[0015] The present invention provides the application of the activated feldspar powder described in the above technical solution in a cement stabilized macadam mixture.
[0016] The present invention provides a feldspar powder cement stabilized macadam mixture, which comprises the following components in parts by mass: 95.5 - 97.5 parts of aggregate, 2.5 - 3.5 parts of cement, and 0.5 - 1.0 part of auxiliary cementitious material, and the auxiliary cementitious material is the activated feldspar powder described in the above technical solution.
[0017] Preferably, the aggregate includes a first aggregate, a second aggregate, a third aggregate, and a fourth aggregate;
[0018] The particle size of the first aggregate is denoted as a, a ≤ 5 mm; the particle size of the second aggregate is denoted as b, 5 mm < b ≤ 10 mm; the particle size of the third aggregate is denoted as c, 10 mm < c ≤ 20 mm; the particle size of the fourth aggregate is denoted as d, 20 mm < d ≤ 30 mm;
[0019] The mass ratio of the first aggregate, the second aggregate, the third aggregate, and the fourth aggregate is 20 - 28:25 - 35:20 - 25:20 - 30.
[0020] The present invention provides a preparation method of an activated feldspar powder, which includes the following steps: calcining a feldspar powder raw material at 1050 - 1300 °C to obtain a calcined feldspar powder; coarsely grinding the calcined feldspar powder to obtain a coarsely ground feldspar powder with a particle size ≤ 1.18 mm; finely grinding the coarsely ground feldspar powder to obtain the activated feldspar powder; the conditions for the fine grinding include: the mass ratio of the coarsely ground feldspar powder to the grinding medium used for fine grinding is 1 - 3:1, the rotation speed is 600 - 900 rpm, and the time is 45 - 75 min. The present invention subjects low-activity feldspar powder solid waste to high-temperature calcination and mechanical grinding, changes the physical and chemical properties of the feldspar powder, improves its cementitious activity, and applies it as an auxiliary cementitious material to a cement stabilized macadam mixture, which can realize the high-value utilization of industrial solid waste, reduce the cement consumption, thereby reducing the production cost, and reduce the exploitation and utilization of non-renewable resources in the raw materials for cement production, thereby protecting the ecological environment and increasing the sustainability of cement. Detailed implementation manners
[0021] The present invention provides a method for preparing active feldspar powder, comprising the following steps:
[0022] calcining the feldspar powder raw material at 1050-1300° C. to obtain calcined feldspar powder;
[0023] The calcined feldspar powder is coarsely ground to obtain coarsely ground feldspar powder with a particle size of ≤1.18 mm;
[0024] The coarsely ground feldspar powder is finely ground to obtain the active feldspar powder; the conditions for the fine grinding include: the mass ratio of the coarsely ground feldspar powder to the grinding body used for fine grinding is 1 to 3:1, the rotation speed is 600 to 900 rpm, and the time is 45 to 75 minutes.
[0025] In the present invention, feldspar powder is a silicate mineral, and its main components are SiO2, Al2O3, Na2O and K2O, etc. Its physical phases mainly include quartz, potassium feldspar and sodium feldspar. Each physical phase has a high degree of crystallinity and extremely stable chemical properties. The present invention uses a composite process of high-temperature calcination and mechanical grinding to activate the gelling activity of feldspar powder to prepare active feldspar powder. If only mechanical grinding is used, the chemical properties of feldspar powder cannot be effectively changed. The present invention applies the active feldspar powder as an auxiliary gelling material to cement-stabilized crushed stone mixture, which is not only conducive to the high-value utilization of industrial solid waste resources, but also provides a new research idea for the high-value recycling of feldspar powder solid waste. At the same time, it can reduce the amount of cement used to reduce production costs, and reduce the exploitation and utilization of non-renewable resources in cement production raw materials, thereby protecting the ecological environment and increasing the sustainability of cement. The method of the present invention is described in detail below.
[0026] The present invention calcines a feldspar powder raw material at 1050-1300° C. to obtain calcined feldspar powder. As an embodiment of the present invention, the feldspar powder raw material includes the following phases: quartz 40-55wt%, albite 40-55wt% and potassium feldspar 4-10wt%; further, the content of the quartz can be specifically 40wt%, 45wt%, 50wt% or 55wt%, the content of the albite can be specifically 40wt%, 45wt%, 50wt% or 55wt%; the content of the potassium feldspar can be specifically 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt% or 10wt%. In the embodiment of the present invention, the chemical composition of the feldspar powder raw material includes: SiO276.4wt%, Al2O314.7wt%, Na2O4.1wt%, K2O2.18wt%, CaO0.7wt%, Fe2O30.2wt%, Li2O0.1wt%, and contains the remaining undetected components. As an embodiment of the present invention, the indicators of the feldspar powder raw material include: particle size ≤1.18mm; specific surface area of 50~200m 2 / kg, specifically 50m 2 / kg, 59m 2 / kg, 80m 2 / kg、100m 2 / kg or 200m 2 / kg; the 28d compressive strength activity index can be 50-65%, specifically 50%, 55%, 58%, 60% or 65%; the 28d flexural strength activity index can be 60-80%, specifically 60%, 65%, 67%, 70% or 80%.
[0027] As an embodiment of the present invention, the feldspar powder raw material can be dried before calcination; the drying temperature can be 100-120° C., specifically 105° C. In the embodiment of the present invention, the drying can be carried out in an oven; the present invention has no special limitation on the drying time, as long as sufficient drying is ensured.
[0028] In the present invention, the calcination temperature is 1050-1300°C, specifically 1050°C, 1100°C, 1150°C, 1200°C, 1250°C or 1300°C. As an embodiment of the present invention, the heating rate to the temperature required for the calcination can be 8-12°C / min, specifically 10°C / min. The present invention can change the phase transition of the crystal structure of the feldspar powder through calcination, increase its amorphous content, and help increase the activity index of the feldspar powder; if the calcination temperature is too low, the gelling activity of the feldspar powder cannot be activated; if the calcination temperature is too high, the feldspar powder will be recrystallized, thereby reducing its activity. As an embodiment of the present invention, the calcination time can be 0.5-1.5h, specifically 1h. In the embodiment of the present invention, the calcination time is controlled within the above range, which can change the crystal structure of the feldspar powder and help increase the amorphous content of the feldspar powder. As an embodiment of the present invention, the calcination can be carried out in an air atmosphere. In the embodiment of the present invention, the calcination can be carried out in a high-temperature furnace.
[0029] After obtaining the calcined feldspar powder, the present invention coarsely grinds the calcined feldspar powder to obtain coarsely ground feldspar powder with a particle size of ≤1.18 mm. The present invention has no special restrictions on the method and conditions of the coarse grinding, and it is sufficient to obtain coarsely ground feldspar powder with a particle size that meets the requirements. In an embodiment of the present invention, the coarse grinding can be specifically carried out in a ball mill. According to the equipment conditions of the ball mill, the calcined feldspar powder can be crushed before the coarse grinding. The present invention has no special requirements on the equipment and operating conditions used for the crushing, and it is sufficient to meet the requirements of the ball mill for coarse grinding; in an embodiment of the present invention, the ball mill for coarse grinding can specifically be a cement test small mill SM-500. The present invention controls the particle size of the coarsely ground feldspar powder within the above range, and can control the uniformity of the particle size of the feldspar powder, thereby shortening the grinding time, improving energy utilization, and reducing the overall processing cost.
[0030] After obtaining the coarsely ground feldspar powder, the present invention finely grinds the coarsely ground feldspar powder to obtain the active feldspar powder. In the present invention, the conditions for the fine grinding include: the mass ratio of the coarsely ground feldspar powder to the grinding body used for fine grinding is 1 to 3:1, specifically 1:1, 2:1 or 3:1; the rotation speed can be 600 to 900 rpm, specifically 600 rpm, 700 rpm, 800 rpm or 900 rpm; the time can be 45 to 75 min, specifically 45 min, 50 min, 55 min, 60 min, 65 min, 70 min or 75 min. In an embodiment of the present invention, the fine grinding can be carried out in a high-energy ball mill, and the high-energy ball mill can be a planetary ball mill YXQM-4L. The present invention performs fine grinding under the above conditions, which can significantly reduce the particle size, increase the specific surface area, and is conducive to improving the reaction rate and degree of reaction with cement hydration products (such as Ca(OH)2).
[0031] The present invention provides an active feldspar powder prepared by the preparation method described in the above technical solution. As an embodiment of the present invention, the indicators of the active feldspar powder include: a specific surface area of 568 to 711 m 2 / kg, specifically 568m 2 / kg, 661m 2 / kg, 672m 2 / kg, 683m 2 / kg or 711m 2 / kg; the 28d compressive strength activity index can be 75-85%, specifically 75%, 77%, 78%, 82% or 85%; the 28d flexural strength activity index can be 87-98%, specifically 87%, 89%, 91%, 93% or 98%. As an embodiment of the present invention, the density of the active feldspar powder can be 2.645-2.650 g / cm 3 , specifically 2.645 g / cm 3 , 2.648g / cm 3 or 2.650g / cm 3 As an embodiment of the present invention, the relative crystallinity of the strongest characteristic peak of each phase in the active feldspar powder includes: the relative crystallinity of the quartz phase is 100%; the relative crystallinity of the albite and potassium feldspar phases is 0-52.3%, further can be 0-43.7%, and further can be 0-31.6%.
[0032] The present invention provides an application of the active feldspar powder described in the above technical solution in a cement-stabilized macadam mixture. As an embodiment of the present invention, the active feldspar powder is used in the cement-stabilized macadam mixture, and the obtained feldspar powder cement-stabilized macadam mixture can be used to prepare the road base of cement-stabilized macadam. The present invention uses a composite process of high-temperature calcination and mechanical grinding to activate the cementitious activity of feldspar powder, and then uses the obtained active feldspar powder as an auxiliary cementitious material in the cement-stabilized macadam mixture, so as to realize the recycling of industrial solid waste, reduce the production cost of cement and reduce the exploitation and utilization of non-renewable resources in the raw materials for cement production. The following is a detailed description.
[0033] The present invention provides a feldspar powder cement-stabilized macadam mixture, which comprises the following components in parts by mass: 95.5-97.5 parts of aggregate, 2.5-3.5 parts of cement, and 0.5-1.0 part of auxiliary cementitious material, and the auxiliary cementitious material is the active feldspar powder described in the above technical solution.
[0034] In parts by mass, the feldspar powder cement-stabilized macadam mixture of the present invention comprises 95.5-97.5 parts of aggregate, which may specifically be 95.5 parts, 96.0 parts, 96.5 parts, 97.0 parts or 97.5 parts. As an embodiment of the present invention, the aggregate may include a first aggregate, a second aggregate, a third aggregate and a fourth aggregate; the particle size of the first aggregate is denoted as a, and a≤5mm; the particle size of the second aggregate is denoted as b, and 5mm < b≤10mm; the particle size of the third aggregate is denoted as c, and 10mm < c≤20mm; the particle size of the fourth aggregate is denoted as d, and 20mm < d≤30mm; the mass ratio of the first aggregate, the second aggregate, the third aggregate and the fourth aggregate may be 20-28:25-35:20-25:20-30, specifically 24:28:23:25. In the embodiments of the present invention, the aggregate with the above gradation is used, which can increase the skeleton interlocking effect of the mixture and is beneficial to improving the road performance of the mixture.
[0035] Based on the parts by mass of the aggregate, the feldspar powder cement-stabilized macadam mixture of the present invention comprises 2.5-3.5 parts of cement, which may specifically be 2.5 parts, 2.8 parts, 3.0 parts, 3.2 parts or 3.5 parts. As an embodiment of the present invention, the type of the cement may be ordinary Portland cement P.O 42.5.
[0036] Based on the mass fraction of the aggregate, the feldspar powder cement stabilized gravel mixture of the present invention includes 0.5 to 1.0 parts of auxiliary cementitious materials, specifically 0.5 parts, 0.6 parts, 0.7 parts, 0.8 parts, 0.9 parts or 1.0 parts; the auxiliary cementitious material is the active feldspar powder described in the above technical solution. The present invention uses the active feldspar powder as an auxiliary cementitious material for cement stabilized gravel mixture, which can replace 20wt% of cement, is conducive to reducing production costs, and can achieve high-value resource utilization of industrial solid waste.
[0037] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0038] The indicators of the feldspar powder raw materials used in the following experiments are shown in Table 1.
[0039] Table 1 Indicators of feldspar powder raw materials
[0040]
[0041] Example 1
[0042] The feldspar powder raw material is placed in an oven at 105°C and dried to obtain dry feldspar powder;
[0043] The dried feldspar powder is placed in a high temperature furnace, heated from room temperature to 1200° C. at a heating rate of 10° C. / min in an air atmosphere and calcined for 1 hour to obtain calcined feldspar powder;
[0044] The calcined feldspar powder is crushed and then coarsely ground using a ball mill (specifically a cement test small mill SM-500) to obtain coarsely ground feldspar powder with a particle size of ≤1.18 mm;
[0045] The coarsely ground feldspar powder is placed in a high-energy ball mill (specifically a planetary ball mill YXQM-4L) for fine grinding, wherein the conditions for the fine grinding include: a mass ratio of the coarsely ground feldspar powder to the grinding body of the high-energy ball mill is 2:1, a rotation speed of the high-energy ball mill is 800 rpm, and a fine grinding time is 75 min; after the fine grinding, active feldspar powder is obtained.
[0046] Embodiments 2 to 5
[0047] The method of Example 1 is used for operation, except that the calcination temperature and / or fine grinding time are different, which are specifically listed in Table 2.
[0048] Comparative Example 1
[0049] The method of Example 1 was followed, except that calcination, coarse grinding and fine grinding were omitted, as specifically listed in Table 2, i.e., the target product in this comparative example was the dry feldspar powder in Example 1.
[0050] Comparative Example 2
[0051] The method of Example 1 was used, except that calcination and coarse grinding were omitted, and the fine grinding time was 30 min, as specifically listed in Table 2, that is, in this comparative example, the dry feldspar powder described in Example 1 was directly finely ground for 30 min to obtain the target product (the dry feldspar powder was not calcined, and its particle size met the fine grinding requirements, so no coarse grinding was required).
[0052] Comparative Example 3
[0053] The method of Example 1 was used, except that calcination and coarse grinding were omitted, and the fine grinding time was 75 min, as specifically listed in Table 2, that is, in this comparative example, the dry feldspar powder described in Example 1 was directly finely ground for 75 min to obtain the target product (the dry feldspar powder was not calcined, and its particle size met the fine grinding requirements, so no coarse grinding was required).
[0054] Comparative Example 4
[0055] The method of Example 1 was used, except that the calcination temperature was 800°C and the coarse grinding was omitted, as specifically listed in Table 2, that is, in this comparative example, the calcined feldspar powder obtained under low-temperature calcination conditions was directly finely ground to obtain the target product (the calcination temperature was low, and the particle size of the calcined feldspar powder obtained met the fine grinding requirements, so no coarse grinding was required).
[0056] Comparative Example 5
[0057] The method of Example 1 was used, except that the calcination temperature was 1000°C and the coarse grinding was omitted, as specifically listed in Table 2, that is, in this comparative example, the calcined feldspar powder obtained under low-temperature calcination conditions was directly finely ground to obtain the target product (the calcination temperature was low, and the particle size of the calcined feldspar powder obtained met the fine grinding requirements, so no coarse grinding was required).
[0058] Table 2 Preparation process and conditions in each embodiment and each comparative example
[0059]
[0060]
[0061] Test Example 1
[0062] The performance of the target products in each embodiment and comparative example was tested according to the method specified in "Pozzolanic Mixtures for Cement" (GB T 2847-2022), and the specific test results are shown in Table 3. As shown in Table 3, the active feldspar powders prepared in Examples 1 to 3 have a high activity index, and the active feldspar powder prepared in Example 1 has all its sodium feldspar and potassium feldspar phases converted into amorphous state, with a specific surface area of 711m 2 / kg, the 28d compressive strength activity index is 85%, and the 28d flexural strength activity index is 98%, which is significantly better than the target product prepared in the comparative example.
[0063] Table 3 Performance test results of target products in various embodiments and comparative examples
[0064]
[0065] Note: Assuming that the relative crystallinity of each mineral phase in the original ore is 100%, the relative crystallinity and amorphization degree of each mineral phase before and after activation are calculated according to the formulas shown in Formula 1 and Formula 2:
[0066]
[0067] Where: η is the relative crystallinity of each mineral phase in feldspar powder; θ is the amorphization degree of each mineral phase in feldspar powder; I milled is the diffraction peak intensity of the strongest characteristic peak of each mineral phase in the activated feldspar powder (expressed as the integrated area under the diffraction peak); I raw It is the diffraction peak intensity of the strongest characteristic peak of each mineral phase in feldspar powder (expressed as the integrated area under the diffraction peak).
[0068] Test Example 2
[0069] According to the "Testing Procedure for Stabilized Materials of Inorganic Binders for Highway Engineering" (JTG 3441-2024), the target products in Example 1, Example 3, Example 5 and Comparative Example 1, Comparative Example 3, and Comparative Example 5 are applied to cement-stabilized gravel mixtures and formed into cement-stabilized gravel cylindrical specimens with a size of 150×150 mm. The cement content in the base mix of the cement-stabilized gravel mixture is 3.5wt%, and the percentages of 0-5mm, 5-10mm, 10-20mm and 20-30mm grade aggregates in the total mass of the aggregates are 24%, 28%, 23% and 25%, respectively. The cement content in the mix of the cement-stabilized gravel mixture of the control group is 2.8wt%, the particle size and mass ratio of the aggregates remain unchanged, and the mass percentage of the target products in the above-mentioned embodiments and comparative examples is 0.7%. The formed cement-stabilized crushed stone cylindrical specimens were sealed and placed in a standard curing room with a temperature of 20±2℃ and a relative humidity of 98% for curing, and immersed in a 20±2℃ water tank for 24 hours on the last day. Then, the compressive strength and splitting strength at 7d and 28d were tested according to JTG 3441-2024. The specific results are shown in Table 4.
[0070] Table 4 Test results of feldspar powder cement stabilized crushed stone mixture
[0071]
[0072] It can be seen from Table 4 that, compared with the feldspar powder prepared in Comparative Examples 1, 3 and 5, the compressive strength and splitting strength of the prepared cement-stabilized crushed stone cylindrical specimens can be significantly improved by replacing 20% of cement with the active feldspar powder in Example 1, 3 and 5. Taking Example 1 and Comparative Example 1 as examples, the feldspar powder prepared in Comparative Example 1 is used, and the 7d and 28d splitting strengths of the obtained cement-stabilized crushed stone cylindrical specimens are 75.8% and 76.4% of the benchmark group, and the 7d and 28d compressive strengths are 72.3% and 72.9% of the benchmark group. Using the active feldspar powder in Example 1, the 7d and 28d splitting strengths of the obtained cement-stabilized crushed stone cylindrical specimens reach 95.2% and 98.6% of the benchmark group, respectively, and the 7d and 28d compressive strengths reach 89.4% and 91.5% of the benchmark group, respectively. Compared with the feldspar powder prepared in Comparative Example 1, the 7d and 28d splitting strengths of the cement-stabilized crushed stone cylindrical specimens obtained by using the active feldspar powder in Example 1 were increased by 25.5% and 29.1%, respectively, and the 7d and 28d compressive strengths were increased by 23.5% and 25.6%, respectively. Therefore, the feldspar powder method of the present invention can effectively improve the gelling activity, and the 20wt% cement in the cement-stabilized crushed stone mixture can be replaced by the feldspar powder, and the 7d and 28d compressive strengths and splitting strengths are close to those of the reference group.
[0073] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A preparation method of active feldspar powder, comprising the following steps: Calcining the feldspar powder raw material at 1050 - 1300 °C to obtain calcined feldspar powder; Coarsely grinding the calcined feldspar powder to obtain coarsely ground feldspar powder with a particle size ≤ 1.18 mm; Finely grinding the coarsely ground feldspar powder to obtain the active feldspar powder; The conditions for the fine grinding include: the mass ratio of the coarsely ground feldspar powder to the grinding medium used for fine grinding is 1 - 3:1, the rotation speed is 600 - 900 rpm, and the time is 45 - 75 min.
2. The preparation method according to claim 1, characterized in that: The feldspar powder raw material comprises the following phases: quartz 40 - 55 wt%, albite 40 - 55 wt%, and orthoclase 4 - 10 wt%.
3. The preparation method according to claim 1 or 2, characterized in that: The indicators of the feldspar powder raw material include: particle size ≤ 1.18 mm, specific surface area of 50 to 200 m 2 / kg, the 28d compressive strength activity index is 50-65%, and the 28d flexural strength activity index is 60-80%.
4. The preparation method according to claim 1, characterized in that: The feldspar powder raw material is dried before calcining; the drying temperature is 100 - 120 °C.
5. The preparation method according to claim 1, characterized in that: The calcining time is 0.5 - 1.5 h; the calcining is carried out in an air atmosphere.
6. The active feldspar powder prepared by the preparation method according to any one of claims 1 - 5.
7. The active feldspar powder according to claim 6, characterized in that: The indicators of the active feldspar powder include: specific surface area of 568-711m 2 / kg, the 28d compressive strength activity index is 75-85%, and the 28d flexural strength activity index is 87-98%.
8. The application of the active feldspar powder according to claim 6 or 7 in a cement stabilized macadam mixture.
9. A feldspar powder cement stabilized macadam mixture, by mass, comprising the following components: aggregate 95.5 - 97.5 parts, cement 2.5 - 3.5 parts, and auxiliary cementitious material 0.5 - 1.0 part, wherein the auxiliary cementitious material is the active feldspar powder according to claim 6 or 7.
10. The feldspar powder cement stabilized crushed stone mixture according to claim 9, characterized in that: The aggregate comprises a first aggregate, a second aggregate, a third aggregate, and a fourth aggregate; The particle size of the first aggregate is denoted as a, a ≤ 5 mm; the particle size of the second aggregate is denoted as b, 5 mm < b ≤ 10 mm; the particle size of the third aggregate is denoted as c, 10 mm < c ≤ 20 mm; the particle size of the fourth aggregate is denoted as d, 20 mm < d ≤ 30 mm; The mass ratio of the first aggregate, the second aggregate, the third aggregate, and the fourth aggregate is 20 - 28:25 - 35:20 - 25:20 - 30.